First record of the frog parasite genus Batrachomyia Krefft from New Guinea (Diptera: Chloropidae) - Evenhuis, Neal (Zootaxa, 2006)
A new species of Batrachomyia, B. krausi, n. sp., from Oya Tabu, Fergusson Island off the southeastern coast of Papua New Guinea is described and illustrated. It marks the first record of this genus of frog parasites outside of Australia. The larva of B. krausi was found parasitizing the frog Rana supragrisea, the first record of the fly genus from the frog family Ranidae. The biology of this species is summarized and a table of known hosts for the genus is given.